Comprehensive patterns of culture consumption in Hungary (How do Hungarians consume culture?) - Pavluska, Valéria (Marketing & Menedzsment, 2019)
THE AIMS OF THE PAPER Our research focuses on two questions: - Have any general types of consumer or any characteristic features of the consumption of culture by the Hungarian population emerged over the last thirty years? - What trends can be seen in the cultural stratification of society in this same period? METHODOLOGY To answer these questions, we first offer a summary of the theoretical models (mainly sociological) which deal with cultural stratification. This is followed by a comparative analysis of culture consumption patterns defined by the most remarkable comprehensive Hungarian cultural research between the middle 1980s and the end of the first decade of the new millennium, together with the patterns defined by the author from a relatively large sample primary research exercise undertaken in 2013. We also analysed the trends visible in these patterns. RESULTS AND RECOMMENDATIONS IN The analyses reveal that the currently prevailing types of culture consumption have basically been visible since the begimiing of the period in question; the only changes were of proportion, and these moved in the direction of the consumption patterns of entertainment culture and cultural passivity. Consequently, several major types seem to have stabilised their position in the socio-cultural stratification of Hungarian society: - the largest group is that of the culturally passive (although within this we can differentiate the old and new types of ''stay-at-home ’ consumers and the non-consumer group), - the increasingly differentiated classical cultural elite, with a waning proportion - cultural omnivores - the entertainment-oriented group (which can be further differentiated) These comprehensive behaviour types of consumption offer a general indication to the culture mediating institutions and other decision-makers of the particular sectors which match the cultural interests of the Hungarian population, and, within this, of the general form and level of participation in institutionalised cultural activities. Concrete decisions, however, need more information, and this can be drawn from research focused on actual preferences related to the different genres of culture and to the prevailing trends of taste in the different fields. However, for precise information, analyses at local level and focusing on the given target audiences also need to be carried out. It is also worth considering some issues in the methodology of culture consumption research, such as e.g. selection of appropriate cultural indicators, development of total analysing apparatus of popular genres, review of ICT on culture consumption and a more extensive exploration of non-consumption.